Investigating the drivers for antibiotic use and misuse amongst medical undergraduates–perspectives from a Sri Lankan medical school - Yasasuru Jayawardhana; Avanthi Premaratne; Sudeepa Kalpani; Sawindya Jayasundara; Gihan Jayawardhane; Chamini Jayawarna; Sarala Gamage; Kalana Jayawardhana; Radshana Johnsan; Chasith Jayasundara; Veranja Liyanapathirana (PLOS Global Public Health, 2023)
Medical undergraduates are a unique group who gain the theoretical knowledge on prescribing antibiotics but are not authorized to prescribe till full licensure. This unique situation may result in self-medication and unauthorized prescription of antibiotics. This cross-sectional study was conducted among medical students of the Faculty of Medicine, University of Peradeniya, Sri Lanka in 2021 to identify patterns and drivers for antibiotic use and misuse among medical undergraduates. A validated, self-administered Google forms-based online questionnaire was used to gather information on antibiotic use, misuse, and associated factors: demographics, knowledge and perceptions. Two scores; a practice score and a knowledge score were calculated to compare with the associated factors. The study population consisted of 347 medical students with a mean age of 24 (SD1.7) years and 142/347 (40.9%) were male participants. The patterns of misuses identified included; use of antibiotics without a prescription (161/347, 46.4%), keeping left-over antibiotics for future use (111/347, 32.0%), not completing the course of antibiotics (81/347, 23.3%), use of left-over antibiotics (74/347, 21.3%), prescribing to animals (61/347, 17.6%), prescribing antibiotics to family members or friends (51/347, 14.7%), antibiotic self-medication (25/347, 7.2%) and not following the dosage regime prescribed (24/347, 6.9%). The practice score ranged from 33% to 100% (median 87%, IQR 80.0–93.3) and did not differ significantly with either the gender or the year of study. The knowledge score ranged from 4% to 100% (median 87%, IQR: 71.5–95.4) differing significantly according to the year of study. Antibiotic prescription by medical undergraduates was perceived as unacceptable (329/347, 94.8%) by the majority. Individual misuse patterns were associated favourably or unfavourably with gender, year of study, having a health care worker at home and knowledge score. The knowledge score increased with the advancement in training at the medical school while the practice score remained indifferent, highlighting the need to identify the additional drivers of antibiotic misuse among medical undergraduates.